LANGUAGE USE BETWEEN MALE AND FEMALE HOST IN HITAM PUTIH TALK SHOW - Nurmaliana Sari; Sumarsih Sumarsih; Busmin Gurning (LINGUISTIK TERAPAN, 2018)
This study discusses about language use occurred by male and female host in Hitam Putih talk show. The method of this research is descriptive qualitative. The subjects of this study are male and female host in Hitam Putih talk show. The data are the utterances produced by male and female host in Hitam Putih talk show. This research focuses on the show broadcasted on October 2016 by taking 4 videos randomly. The objective of this study is to describe kinds of the language use uttered by male and female host in Hitam Putih talk show. The findings showed that the kinds of language use consist of 6 parts. The dominant language use uttered by male host is expletive, because male’s utterances are frequently stated in a negative connotation. On the other hand, female host utterances are found in specialized vocabulary as the most dominant because female host has more interest in talking family affairs, such as the education of children, clothes, cooking, and fashion, etc. Women also tended to talk about one thing related to the home and domestic activities. However, the representation of language use uttered by male and female are deficit, dominance and different. Keywords: Language Use, Gender, Talk Show